Subject and power in Sevgi Soysal’s novels - Atik, Egem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
This thesis explores the relationship between subject and power in Sevgi Soysal’s novels, entitled Yürümek, Yenişehir’de Bir Öğle Vakti and Şafak, with a focused examination of the characters. The process of subjectification that the characters of Sevgi Soysal’s novels undergo are discussed and explored in the study; it is asserted that this subjectification is imposed upon these characters by power, in order for them to be disciplined and subjugated By exhibiting this subjectification process, the author emphasizes that power does not only oppress people by using visible means such as the police, the military or the court of law, but interferes with their identity to make them comply and conform; this also lets the author point out her criticism towards power structures. The thesis takes the problem of transformation, which is prominent in all of Soysal’s novels, as an attempt to change the boundaries of the subjects imposed by the powers that be and interprets it as a pursuit of a resistance against power. The fact that this transformation cannot take place easily both proves that subjects cannot simply get rid of the power’s oppression they have internalized, and points out that the characters are portrayed realistically. Despite all difficulties, the characters studied in this thesis grow concerned about the fact that power, which puts boundaries upon them using certain generalized identities, dominates other people as well. The thesis examines the idea that the characters are inclined to take responsibility for society’s struggles, and to transform this struggle against power into an endeavour embracing and involving all the people whom the arms of power reach.